How to compare cardiovascular disease and risk factors in elderly patients with haemophilia with the general population. (September 2016) - Berger, K.; Schopohl, D.; Lowe, G.; Holme, P. A.; Tait, R. C.; Combescure, C.; Rauchensteiner, S.; Klamroth, R.
Abstract : Introduction: Studies on the prevalence of cardiovascular disease (CVD) and risk factors in patients with haemophilia (PWH) in comparison to the general population have generated inconsistent results. The ADVANCE Working Group collected data on CV comorbidities in PWH aged ≥40 years (H 3 Study). Aim: Identification of German epidemiological data on CVD for the general population, evaluation for appropriateness, and execution of comparisons with PWH. Methods: Identification of data sources by structured literature (EMBASE, MEDLINE) searches. Inclusion criteria: German general population, CVD and risk factors, gender/age stratification, sample size >500 male persons, age groups ≥40 years, current data collection, language English/German. Comparison of data on CVD and risk factors in PWH (H 3 Study) with published German general population data. Results: Criteria for data source appropriateness were defined. Of five national and three international epidemiological studies, the DEGS1 Study (German Health Interview and Examination Survey for Adults) was identified as the most suitable comparator. Compared with men from DEGS1, hypertension was significantly more prevalent in PWH aged 50–59 years (41.7% [95% CI: 37.3–46.2] vs. 52.0% [95% CI: 43.7–60.1], P = 0.03). Coronary artery/heart disease (CHD) was significantly less prevalent in PWH aged ≥60 years (60–69 years: 19.5% [95% CI: 15.9–23.7] vs. 8.1% [95% CI: 3.3–16.1], P = 0.02; 70–79 years: 30.5% [95% CI: 25.9–35.5] vs. 11.8% [95% CI: 5.2–21.9], P = 0.002). No statistically significant difference for ischaemic cerebrovascular disease/stroke was detected. Conclusion: Increased prevalence of hypertension in PWH should trigger regular screening. CHD does occur in PWH aged ≥60 years though apparently with lower prevalence. Given the growing population of elderly PWH, guidelines for prevention and treatment of CVD should be developed.